+0  
 
0
113
2
avatar+115 

If 

f(x) = The sq root of x^9 + 9

,

 express f as the composition of two functions. (The function is of the form 

f(x) = g(h(x)).)

 

g(x) = sq root of x

 

h(x) =

 Apr 25, 2020
 #1
avatar+21953 
+1

If:            h(x)  =  x9 + 9

and         g(x)  =  sqrt(x)

then  g( h(x) )  =  sqrt( x9 + 9 )

 Apr 25, 2020
 #2
avatar+115 
+1

we are trying to find h(x) though. In your answer you gave h(x) We don't know that. The final answer you gave was the problem we started with sqrt of x^9+9

edit- Okay I see now how you got hx I was confused at first. Thanks.

 Apr 27, 2020
edited by Shaezy  Apr 27, 2020

61 Online Users

avatar
avatar